Too many frogs! - Hassett, Ann (Ann M.); Hassett, John. (Boston : Houghton Mifflin Books for Children, 2011)
Nana Quimby, left with a houseful of frogs after the plumber clears the water out of her cellar, proceeds with her attempts to bake a cake, but she must call on the neighborhood children for help when the hopping, thumping, and croaking get to be too much for her.
Horn Book
Kirkus Review
Publisher's Weekly
Horn Book, July 2011
Kirkus Review, June 2011
Publisher's Weekly, May 2011
Keywords: Frogs -- Juvenile fiction; Frogs -- Fiction; Frogs -- Fiction; Picture books for children